Financial decisions and sustainable cash flows in Nigerian manufacturing companies - Japhet Osazefua Imhanzenobe; Semiu Babatunde Adeyemi (International Journal of Management, Economics and Social Sciences (IJMESS), 2020)
This study aimed to identify the effect of some financial decisions that revolve around the assets of the firm on sustainable cash flows. For the financial performance of companies to be sustainable, they ought to generate sustainable cash flows over time because dividends and other appropriations are often paid from net cash flows. Sustainable cash flow was measured using the free cash flow yield. Data on leverage, revenue from asset utilization, and dividend policy of companies were extracted and their relationships with the free cash flow yield were examined. The fully modified OLS (FMOLS) was used to analyze a panel data set of 17 firms listed on the Nigerian Stock Exchange from 2008 to 2016. Asset turnover was found to be positive and significant while debt-to-equity ratio and dividend payout were both found to be negative and significant indicators of sustainable cash flows. Shareholders were advised to moderate their appetite for dividends to make sustainable funds more available. Managers were also advised to promote investment policies that generate positive net cash flows and avoid excessive use of debt to cover deficits in asset financing.
Keywords: M41; 330; Sustainable cash flows; financial sustainability; leverage; dividend policy; free cash flow theory; Modigliani and Miller theory